Species' traits and taxonomic distance can predict the hatching phenology of ostracod (Crustacea) resting eggs from tropical floodplain lakes. Issue 5 (4th October 2021) - Rosa, Jonathan; Petsch, Danielle K.; Martens, Koen; Higuti, Janet
Abstract: Freshwater ostracods are commonly found in temporary ponds and lakes, surviving drought periods by producing resting eggs. We investigated the hatching phenology of ostracod resting eggs from the sediments of temporary floodplain lakes, considering both the taxonomic distance between species and their functional traits, such as carapace size (length and height) and shape, valve ornamentation, and reproductive mode. In addition, we tested the hypotheses: (1) that the hatching time is more similar between congeneric ostracod species than between noncongeneric species; (2) that differences in hatching time between congeneric species are often related to differences in functional traits; (3) that both species composition and functional traits composition of hatchlings change over the incubation time, but with a reduction in the variability over time. The experiment was conducted for 98 days in the laboratory, and the microcosms were monitored weekly. The first hatching of an ostracod was recorded during the second week of incubation after hydration of the sediments. A total of 12 ostracod species hatched, belonging to the families Cyprididae and Candonidae. The above three hypotheses were corroborated. The time between inundation and first hatching was mostly similar for congeneric species in the genus Chlamydotheca, but was different between some species of Strandesia, which might be owing to differences in functional traits. The species composition and functional trait composition of the hatched ostracods were significantly different over the 14 weeks of incubation due to the different hatching phenology of different species. Furthermore, our results show that both taxonomic distance and functional traits can influence the hatching time of ostracod resting eggs from temporary floodplain lakes. Thus, future studies addressing the hatching phenology of ostracod resting eggs (and resting stages from other invertebrates) should also emphasize the use of functional traits.